Fluorinated Organic Electro‐Optic Quinolinium Crystals for THz Wave Generation. Issue 4 (11th January 2019) - Kim, Se‐In; Kang, Bong Joo; Jeong, Chan‐Uk; Shin, Myeong‐Hoon; Kim, Won Tae; Jazbinsek, Mojca; Yoon, Woojin; Yun, Hoseop; Kim, Dongwook; Rotermund, Fabian; Kwon, O‐Pil
Abstract: Fluorinated electro‐optic crystals with state‐of‐the‐art second‐order nonlinear optical response and excellent characteristics for terahertz (THz) wave generation are reported. The fluorinated organic ionic crystals consist of optically highly nonlinear fluorinated HM6FQ (6‐fluoro‐2‐(4‐hydroxy‐3‐methoxystyryl)‐1‐methylquinolinium) or HM7FQ (7‐fluoro‐2‐(4‐hydroxy‐3‐methoxystyryl)‐1‐methylquinolinium) cations and 4‐methylbenzenesulfonate (T) counter anions. Compared to benchmark electro‐optic crystals based on nonfluorinated HMQ (2‐(4‐hydroxy‐3‐methoxystyryl)‐1‐methylquinolinium) cations, introducing fluorine substituent on HM6FQ cations creates additional hydrogen bonds (ArF···HC). Such a molecular engineering leads to an enhanced thermal stability and significant modulations of phonon vibrational modes of crystals in THz frequency region, while excellent π–π stacking and space filling characteristics of HM6FQ cations in crystals lead to state‐of‐the‐art diagonal component of the macroscopic nonlinear optical susceptibility, similar to the case of HMQ cations. HM6FQ‐based crystals exhibit a very high optical‐to‐THz conversion efficiency, comparable to benchmark HMQ‐based crystals. In addition, due to additional hydrogen bonds induced by fluorine substituents, the spectral shape of the generated THz wave is remarkably modified; e.g., the largest spectral gap is near 1.5 and 2.0 THz for HM6FQ‐ and HMQ‐based crystals, respectively. The fluorinated cationic engineering on nonlinear optical crystals having benchmark nonlinear optical response is, as far as is known, reported for the first time. Abstract : The fluorinated organic electro‐optic crystals provide state‐of‐the‐art macroscopic nonlinear optical responses, enhanced thermal stability, and excellent THz wave generation characteristics with significantly modulated THz spectral shape compared to nonfluorinated benchmark nonlinear optical organic crystals.